Developing applications with Java and UML - Reed, Paul R. (Addison-Wesley, 2002)
Developing Applications with Java & trade; and UML focuses on the craft of creating quality Java software. The book introduces the fundamentals of the Unified Modeling Language (UML) and demonstrates how to use this standard object-oriented notation to build more robust Java applications that fulfill users' requirements and stand the test of time. The book features the Rational Unified Process, using a large-scale application to illustrate the development process: how to establish a sound project plan, gather application requirements using use cases, create a successful Java design with UML, and implement Java code from the UML class and sequence diagrams. This sample application showcases the latest Java technology frameworks, including Java Server Pages & trade; (JSP), servlets, and the Enterprise Java Beans & trade; (EJB) 2.0 server-side technology. You will learn how to: Estimate with accuracy and confidence projects built using the use case approach Map UML to Java-based deliverables Understand and describe application requirements using UML use cases Create a design based on UML class and sequence diagrams Use Rational Rose to create and track UML artifacts and generate skeletons for component code Build server-side Java functionality using JSP, servlets, and EJB 2.0 beans Produce code using several options, including JavaBeans, EJB Session Beans, and EJB Entity Beans (using both Bean-Managed Persistence and Container-Managed Persistence) Explore the benefits of deploying Java applications on both open-source and commercial application server products Based on the author's extensive professional experience and the most advanced software development methods, Developing Applications with Java & trade; and UML teaches you how to use UML and the latest developments in technology to create truly successful, professional-quality Java applications. 0201702525B09042001